Organizational Theory in the Context of Contemporary Practices: A Literature Review - Ermiati, Ermiati; Satriya, Guntur; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to explore the contributions of organizational theories to the understanding of modern organizational behavior, with particular focus on organizational culture, leadership, employee engagement, knowledge management, and perceived organizational support (POS). Utilizing a systematic literature review approach, this article synthesizes findings from recent high-impact scholarly publications. The results indicate that organizational culture has a direct influence on employee engagement and fosters organizational identification. Leadership styles, particularly servant and adaptive leadership, are shown to be effective in managing cultural change and reducing resistance within organizations. Moreover, perceived organizational support plays a pivotal role in reducing workplace conflict, enhancing trust, and strengthening employees' emotional commitment. The study also highlights the strategic importance of structured knowledge management in driving innovation and organizational efficiency. Overall, this literature synthesis offers a multidimensional understanding of how organizational theories can inform effective and sustainable managerial strategies. The findings provide practical implications for organizational leaders to cultivate a supportive, adaptive, and knowledge-driven work environment.